Sulitnya Mensejahterakan Masyarakat Suku Baduy Dalam Pendidikan: Difficulties in Advancing The Welfare of The Baduy Tribe in The Field of Education - Tiara Sari Dewi; Wahyuni Retnowulandari (Reformasi Hukum Trisakti, 2024)
Island Java still tribes that uphold traditional rules and preserve them, one of which is in Ds. Kanekes, District. Leuwidamar, Kab. Lebak, Banten Province, namely the Baduy tribe. This is also the reason why it is difficult to provide formal education to children in the Baduy tribe, namely because people still believe that formal education is something that is not good for children. The problem is: how is the fulfillment of child welfare related to education in the Baduy tribe compatible with Law Number 4 of 1979 concerning Child Welfare? What are the efforts made by the government in developing children's education in the Baduy tribe? The type of research used is Sociolegal. The nature of the research is descriptive. Inductive method of drawing conclusions. The factor that makes it difficult to provide formal education in the Baduy tribe is because according to their customs education is prohibited and is a threat to their culture. The government has tried and tried to provide educational assistance such as sending teachers and providing assistance in the form of reading materials for children in the Baduy tribe. However, until now this has been difficult to accept.